Potensi Pasar Ciplukan terhadap Perekonomian Masyarakat di Desa Wisata Lembah Dongde Mojogedang Karanganyar - Pontianus Kuswiyata; Erna Wigati (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Analysis of The Potential of The Ciplukan Market on The Community Economy in The Tourism Village of The Dongde Valley of Mojogedang Karanganyar. This study aims to determine the origin and events that have been held in the ciplukan market and the influence of the ciplukan market on the economy of the Dongde Valley tourism village community. The method used by the research is a qualitative method by conducting observations and interviews with Pokdarwis management with the aim of knowing the potential of the ciplukan market for the economy of the Dongde Valley Tourism Village community. The result of the research is the Ciplukan Market was formed from the proposal of one of the college companions when providing assistance by utilizing an unorganized yard. Ciplukan Market experienced several activities or events such as the launching of the Tourism village, the judging of the Tourism Village, The Telo Festival and The Goat Festival. Of the several potentials developed in the Ciplukan Market, it has had a tremendous influence on the economy of the Dongde Valley tourism village community. The community gets additional income the village also gets income from the ciplukan market income.